Prevention of viral transmission during lung transplantation with hepatitis C-viraemic donors: an open-label, single-centre, pilot trial. Issue 2 (February 2020) - Cypel, Marcelo; Feld, Jordan J; Galasso, Marcos; Pinto Ribeiro, Rafaela V; Marks, Nikki; Kuczynski, Magdalena; Kumar, Deepali; Bahinskaya, Ilona; Bagnato, Vanderlei S; Kurachi, Cristina; Slutsky, Arthur S; Yeung, Jonathan C; et al.
Summary: Background: A substantial proportion of organ donors test positive for hepatitis C virus (HCV) infection. To date, only a few studies have evaluated the safety of using lungs from these donors for transplantation, and no direct interventions to donor organs have been done with the aim of preventing HCV transmission via organ transplantation. We aimed to assess the safety and efficacy of lung transplantation in humans from HCV-positive donors to HCV-negative recipients after application of ex-vivo lung perfusion (EVLP) plus ultraviolet C (UVC) perfusate irradiation. Methods: We did a single centre, prospective, open-label, non-randomised trial in which donor lungs from HCV-viraemic donors (HCV-positive) were transplanted into HCV-negative recipients at Toronto General Hospital, University Health Network (Toronto, ON, Canada). Donors were younger than 65 years old and tested positive for HCV by nucleic acid testing. Donors who tested positive for hepatitis B virus, HIV, human T-lymphotropic virus 1 or 2 were excluded. Recipients were on the lung transplant waiting list without significant liver disease (stage 2 fibrosis or higher were excluded) or active HCV infection. Before implantation, all HCV-positive donor lungs were treated with EVLP with or without UVC perfusate irradiation to reduce the concentration of HCV RNA and infectivity. For the first week after transplantation, patients' HCV RNA blood concentrations were measured once daily, then once per week for 12 weeks. All patients received 12 weeks of oral sofosbuvir 400 mg plus velpatasvir 100 mg, starting at least 2 weeks after transplantation. The primary endpoint was a composite of survival and HCV-free status at 6 months after transplantation in all patients who received HCV-positive lungs. Patient outcomes such as survival, time in hospital, and incidence of acute rejection were compared between those receiving HCV-positive lungs and all patients who received HCV-negative lung transplants during the study period. The study is registered with ClinicalTrials.gov, NCT03112044 . Findings: From Oct 1, 2017, to Nov 1, 2018, 209 patients had a transplantation; of 27 donors who were HCV-positive and initially considered, 22 were suitable for transplantation. The remaining 187 donors were HCV-negative. Before implantation, 11 of the HCV-positive donor lungs were treated with EVLP alone and the other 11 were treated with EVLP plus UVC. Lung disease, urgency status, and positive donor-recipient HLA crossmatch were similar between the patients who received HCV-positive and HCV-negative lungs. 20 (91%) patients in the HCV-positive group developed HCV viraemia within the first week after transplantation and had sofosbuvir plus velpatasvir treatment, starting at a median of 21 days after transplantation (IQR 16·76–24·75). Donor organ treatment with EVLP plus UVC was associated with significantly lower recipient viral loads in blood within the first week after transplantation than with EVLP alone (median of 167 IU/mL [IQR 20–12 000] vs 4390 IU/mL [1170–112 000] at day 7; p=0·048) and prevented transmission in two (18%) of 11 patients. All 20 infected patients achieved negative HCV PCR within 6 weeks of treatment initiation. The primary endpoint of survival and HCV-free status at 6 months after transplantation was achieved in 19 (86%) of 22 patients in the HCV-positive group. 6-month survival was 95% in recipients receiving lungs from HCV-viraemic donors versus 94% in recipients receiving lungs from HCV-negative donors. The most common grade 3–4 adverse events in the HCV-positive group were respiratory complications (five [23%]) and infections (four [18%]). Serious adverse events requiring admission to hospital occurred in ten (45%) patients. One (5%) patient who did not develop HCV infection died at day 31 from multiorgan failure related to pseudomonas sepsis. Two patients presented with HCV relapse within 3 months after sofosbuvir plus velpatasvir completion and required retreatment. Interpretation: Early and intermediate clinical outcomes were not significantly different between patients receiving viraemic HCV donor lungs and HCV-negative donor lungs. Donor organ treatment with UVC perfusate irradiation during EVLP significantly decreased HCV viral loads within the first 7 days after transplantation and shows the proof-of-concept for a novel approach of minimising viral load ex vivo before transplantation, with intent of preventing donor–recipient transmission. Funding: Canadian Institutes of Health Research.